Challenges to conducting randomised controlled trials with adults with intellectual disabilities: Experiences of international experts. Issue 3 (5th December 2020) - Mulhall, Peter; Taggart, Laurence; McAloon, Toni; Coates, Vivien
Abstract: Background: Globally, conducting randomised controlled trials can be a complex endeavour. The complexity increases when including participants with cognitive or intellectual disabilities. A fuller understanding of the barriers and challenges that can be expected in such trials may help researchers to make their trials more inclusive for people with disabilities. Method: Semi‐structured interviews were conducted with twelve international trial experts. Results: Eight themes emerged relating to challenges linked to: 1) participant co‐morbidities, 2) participant ability levels, 3) ethics and consent, 4) the RCT methodology, 5) gatekeeping, 6) staff turnover, 7) lack of technical understanding and 8) attitudes and perceptions. Conclusion: Conducting trials with cognitively disabled participants can pose unique challenges although many can be overcome with 'reasonable adjustments'. Challenges that are harder to overcome are attitudes and perceptions that people (professional staff, funding bodies, carers or fellow researchers) hold towards the utility of conducting trials with cognitively disabled populations.